PEMANFAATAN BUAH DURIAN MENJADI BUMBU TEMPOYAK INSTANT (BOTANT) SEBAGAI OLEH-OLEH KHAS JAMBI - Lucky Enggrani Fitri; Rizky Anggreyni; Putti Sherna; Rahmah Rizki Thoyyibah; Rizka Apriliani; Melia Hairunnisa (Yayasan Nusantara Hasana Berdikari, 2023)
Botant is a packaged product containing instant spices ready to use in the context of the use of durian fruit in Batanghari Regency, every year at the end of December, many places are harvesting durian. As in Muara Tembesi, Mersam, Aro Village and Baung Muara Bulian River, Selat Village, Betung Island Village and Ture Village, Pemayung District. Durian prices in the garden range from Rp. 9 to 10 thousand per piece. That's the price of a standard fruit that is the same size as the size of coconut fruit. If it has been sold in other areas, such as the city of Jambi, in addition to the Legit and Sweet taste of the fruit, the distribution costs ranging from the garden to the city, making the price of the durian more expensive, which reaches Rp. 50 thousand per piece. Besides being eaten directly, durian fruit can be processed into a variety of processed preparations that are of quite large value and of course good for health. The advantages of botant in addition to being a processed product of the use of local jambi durian, can also be a characteristic of typical souvenirs of Jambi that is made into curry, where botant as an instant tempoyak spice that can be used to make tempoyak practically without having to enter other complementary spices, Except the flavoring of the taste that is adapted to the taste of consumers, and as an innovation to improve the quality of tempoyak through proper packaging.